2011
DOI: 10.1007/s10120-011-0091-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of CA125 and CA72-4 in gastric cancer with peritoneal dissemination

Abstract: Background Serum tumor markers have been shown to correlate with the clinical status of patients with advanced gastric cancer. However, the clinical significance of each tumor marker in patients with peritoneal dissemination has not been fully verified. Methods Four serum markers, carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19-9, CA125, and CA72-4, were periodically measured in 102 patients with peritoneal dissemination who received combination intravenous and intraperitoneal chemotherapy. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 23 publications
6
106
1
Order By: Relevance
“…The CA72-4 was identified as a tumor marker for late-stage GC in previous studies. Emoto et al (31) determined that the sensitivity of CA72-4 for the peritoneal metastasis of GC was 45%, which was higher compared with that of CEA and CA19-9. Patients with ovarian metastasis exhibited significantly higher levels of CA72-4 (31).…”
Section: Discussionmentioning
confidence: 99%
“…The CA72-4 was identified as a tumor marker for late-stage GC in previous studies. Emoto et al (31) determined that the sensitivity of CA72-4 for the peritoneal metastasis of GC was 45%, which was higher compared with that of CEA and CA19-9. Patients with ovarian metastasis exhibited significantly higher levels of CA72-4 (31).…”
Section: Discussionmentioning
confidence: 99%
“…The serum CA125 levels had high sensitivity (38.6 %), specificity (98.4 %), and diagnostic accuracy (91.5 %). Emoto et al [50] also showed the sensitivities of CA125 for peritoneal metastasis at the initial diagnosis was 46 %. The CA125 level was significantly correlated with the degree of peritoneal dissemination and patient survival [50,55,57].…”
Section: Clinical Significance Of Serum Marker Monitoring During Chemmentioning
confidence: 95%
“…Among these 19 articles, 12 articles indicated that the positive rate for CA72-4 was the highest among the three serum markers ( Table 2). The combination with the highest positive rate was CA19-9 and CA72-4 [15,50]. Because the average frequency of these three markers was approximately 10 % at stage I (CEA = 13.7 %, CA19- Clinical utility of tumor markers in gastric cancer 27 9 = 9.0 %, and CA72-4 = 12.0 %), they may not be useful for early cancer screening.…”
Section: Manuscript Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroscopy with biopsy is currently an efficient method for the diagnosis of gastric cancer, but it is not appropriate for screening gastric cancer because of its discomfort and high cost. The detection of serum tumor markers is simple in cancer screening and diagnosis, but it is difficult to be a conventional method for gastric cancer screening for its poor sensitivity and specificity (Sturgeon et al, 2010), only valuable in the prognostic evaluation of patients with gastric cancer (Dilege et al, 2010;Duraker et al, 2001;Emoto et al, 2012;Li et al, 2011;Ychou et al, 2000). Recently, a lot of studies were performed in serum proteomics and epigenetics and found some new markers with potential clinical significance in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%